Determining factors affecting perceived customer satisfaction on public utility bus system in Occidental Mindoro, Philippines: A case study on service quality assessment during major disruptions - Jou, Yung-Tsan (Animo Repository, 2023)
The imposition of lockdown due to the COVID-19 pandemic has affected the majority of enterprises throughout the globe. The public transportation sector was greatly affected, especially in provincial areas in the Philippines. This study aimed to investigate the service quality of bus transits in Occidental Mindoro during the COVID-19 pandemic using Analytical Hierarchy Process (AHP) and SERVQUAL dimensions. A total of 200 individuals completed a 67-question online questionnaire. AHP was utilized to determine which bus providers need to be improved the most. Then, the SERVQUAL approach was used. The five dimensions were linked with the use of new technologies, including the COVID-19 protocol, service quality, and customer satisfaction as latent variables in structural equation modeling. The AHP results indicated that safety accounts for the most significant weight for bus passengers. Moreover, service quality, responsiveness, reliability, empathy, and COVID-19 protocol significantly enhance service and customer satisfaction. The findings of this research study can now serve as a service quality assessment and guidelines to provide a sustainable public bus transportation; it can also help determine the significant and insignificant factors in enhancing the service quality and improving the customer satisfaction of bus providers worldwide.